Designing an Educational Video About the Dangers of Software Piracy Using 2D-Based Motion Graphic Techniques - Puspitawati, Endah; Prakosa, Herjuna Ardi (Journal of Multimedia Trend and Technology, 2024)
This study explores the potential of 2D animation-based educational videos with motion graphic techniques as a tool to increase public understanding and awareness of the dangers of pirated software. With the increasing prevalence of pirated software that can be easily accessed from various websites, there needs to be an innovative approach to increasing public understanding and awareness of its negative impacts. This study uses pre-production, production, and post-production methods to produce animated videos. The focus of the study is on the use of 2D animation and motion graphics to communicate messages about the risks of pirated software effectively. By utilizing the advantages of 2D animation in efficiency, simplicity, and cost-effectiveness, as well as the ability of motion graphics to combine text and moving images, this study aims to increase public understanding, especially young people, students, and computer users, about the illegal consequences and negative impacts of using pirated software. The results of the study indicate that 2D animation videos with motion graphics can convey complex messages about the dangers of pirated software effectively and attractively.